Comparison of Standard and Right/Left International Knee Documentation Committee Subjective Knee Form Scores. Issue 5 (April 2019) - Magnuson, Justin A.; Strnad, Greg; Smith, Clair; Jones, Morgan H.; Saluan, Paul; Irrgang, James J.; Spindler, Kurt P.
Background: The International Knee Documentation Committee Subjective Knee Form (IKDC-SKF) is a validated patient-reported outcome used in clinical research. No studies exist directly comparing the standard unilateral adult version (IKDC-SKF) with the bilateral adult version (R/L IKDC-SKF). Hypotheses: The first hypothesis is that no clinically relevant difference would be observed between standard IKDC-SKF scores and involved R/L scores. The second hypothesis is that a relevant difference would be observed between involved and uninvolved scores on the R/L IKDC-SKF. Study Design: Cohort study (Diagnosis); Level of evidence, 2. Methods: One hundred patients were enrolled via a crossover study design. Participants were split into 2 groups per simple randomization. One group completed the standard IKDC-SKF first and the R/L IKDC-SKF second. The other group completed forms in the reverse order. A 10-minute washout period was administered between questionnaires. Participants reported their preferred form in a postquestionnaire survey. A 5-point threshold for clinical relevance was set a priori, which is less than multiple published minimal detectable change and minimal clinically important difference metrics of the standard IKDC-SKF, ranging from 6.3 to 20.5. Data were analyzed with Bland-Altman plots, paired t tests, correlations, and chi-square tests. Results: Paired t tests between the standard IKDC-SKF and the involved R/L IKDC-SKF scores demonstrated a statistically significant mean difference of 1.4 ( P = .008; 95% CI, 0.4-2.4). However, the 95% CI falls under the clinically relevant threshold of 5. Standard and involved knee scores from the R/L IKDC-SKF were highly correlated, with a rho of 0.95. Patients consistently distinguished the injured knee from the uninjured knee across a range of scores via the R/L IKDC-SKF ( P < .001). The postquestionnaire survey showed that 55 patients preferred the R/L IKDC-SKF, 30 preferred the standard IKDC-SKF, and 15 had no preference. Post hoc analysis showed a significant preference for "R/L vs standard IKDC-SKF" ( P = .014) and "R/L IKDC-SKF vs no preference" ( P < .003). Conclusion: No clinically relevant difference was observed between the standard IKDC-SKF and the involved knee score of the R/L IKDC-SKF. Therefore, for symptomatic unilateral knee diagnosis, either form can be used. The R/L IKDC-SKF showed a consistent and clinically relevant difference between involved and uninvolved knees. Patients in this study preferred the R/L IKDC-SKF.